2017
DOI: 10.1155/2017/8215726
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Stroke Risk Factors and Warning Signs in Patients with Recurrent Stroke or Recurrent Transient Ischaemic Attack in Thailand

Abstract: Stroke is a global burden. It is not known whether patients who are most at risk of stroke (recurrent stroke or recurrent transient ischaemic attack) have enough knowledge of stroke risk factors and warning signs. The aim of this study was to assess the knowledge of stroke risk factors and warning signs in this high-risk population. We performed a cross-sectional questionnaire-based study of patients with recurrent stroke or recurrent TIA admitted to Srinagarind Hospital and Khon Kaen Hospital, Thailand. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
(40 reference statements)
7
41
4
2
Order By: Relevance
“…20,32 The knowledge about stroke early symptoms which are hardly identified such as confusion, severe headache, paresthesia and vision impairment were identified to score 37.9%, 34.5%, 32.8% and 20% respectively. These findings are in line with the findings of Hickey et al 8 ,Obembe et al 20 , Saengsuwan et al 33 ,Pandian et al 34 stating that only minority of their respondents identified confusion, severe headache and vision impairment as the stroke early symptoms. In contrast, their knowledge about the three elements of FAST, namely Facial drooping, Arm weakness, and Speech disturbance, in this research were correctly identified by as many as 13.8% respondents.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…20,32 The knowledge about stroke early symptoms which are hardly identified such as confusion, severe headache, paresthesia and vision impairment were identified to score 37.9%, 34.5%, 32.8% and 20% respectively. These findings are in line with the findings of Hickey et al 8 ,Obembe et al 20 , Saengsuwan et al 33 ,Pandian et al 34 stating that only minority of their respondents identified confusion, severe headache and vision impairment as the stroke early symptoms. In contrast, their knowledge about the three elements of FAST, namely Facial drooping, Arm weakness, and Speech disturbance, in this research were correctly identified by as many as 13.8% respondents.…”
Section: Discussionsupporting
confidence: 89%
“…The same way goes with gender, which has shown no significant influence in determining the knowledge about stroke risk factors because, according to the research finding, there was no difference in the knowledge of stroke risk factors between female and male respondents. This is confirmed by the research finding of Falavigna et al 30 , Saengsuwan et al 33 which has indicated that there was no correlation between gender and knowledge. In contrast, Amen et al 31 , Chiamaka and Hemamalini 41 , Stroebele et al 42 state that females are the predictors for knowledge about stroke risk factors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Walaupun tidak signifikan, dapat dilihat bahwa pasien yang memiliki durasi menderita hipertensi lebih lama memiliki tingkat pengetahuan lebih baik dibandingkan dengan pasien yang menderita hipertensi kurang dari lima tahun. Hal ini sejalan dengan penelitian yang dilakukan oleh Saengsuwan 21 bahwa tingkat pengetahuan pasien terkait penyakitnya berkorelasi kuat dengan lamanya pasien telah menderita suatu penyakit kronis.…”
unclassified
“…Contrasting with our findings, studies employing surveys with open-ended questions indicated low rates of knowledge. 24,25 Nonetheless, the use of closed-ended questions in the present study might have overestimated the real knowledge levels in some domains. Doctors and other healthcare providers were the major source of information about stroke and its preventive strategies (in 62.2% of patients), in the present study.…”
Section: Methods Design and Settingmentioning
confidence: 74%